Effect of Executive Function on Event-Based Prospective Memory for Different Forms of Learning Disabilities - Ji, Lili; Zhao, Qi; Gu, Huang; Chen, Yanan; Zhao, Junfeng; Jiang, Xiaowei; Wu, Lina (Frontiers in Psychology, 2021)
Students with learning disabilities (LDs) suffer from executive function deficits and impaired prospective memory (PM). Yet the specificity of deficits associated with different types of LDs still unclear. The object of the present research was to compare subgroups of students with different forms of learning disabilities (< 25th percentile) on executive function and PM. Students with a mathematics disability (MD, n = 30), reading disability (RD, n = 27), both (RDMD, n = 27), or neither (typically developing, TD, n = 30) were evaluated on a set of executive functioning tasks (e.g., updating, inhibition and shifting) and on prospective memory. The results showed that students with MDs and RDMDs suffered from PM deﬁcits. Among the subtypes of LDs, the deficit is different. The students with RDMDs showed a wide range of defects in PM, shifting, inhibition, and updating. In comparison, students with MDs experienced deﬁcits in PM and shifting, while students with RDs experienced a deﬁcit only in updating. For the RD group, the RDMD group and the TD group, updating and shifting significantly predicted PM. For the MD group, only shifting significantly predicted PM performance, but PM deficits were not completely confined to shifting deficits.